Analyse biometrie des pointes d’elephants saisies dans le cadre de lutte antibraconnage par les services de la conservation dans le massif du Sud-est Cameroun - Noupa, Paul (Pachyderm, 2005)
This article assesses data from tusks measured during a study focusing on biometric measurements taken on the carcasses of forest elephant poached in southeastern Cameroon. Measurements from 62 tusks suggest that 2 out of 3 elephants poached in this region are young individuals. ’The average tusk weight of the poached elephants examined was 4.44 kg, against an average of 15 kg estimated for the area. Data provides an indicator of the type of offtake in the area and its potential impact on the population as a whole. This analysis ’provides evidence that sexual diamorphism becomes apparent in young elephants when the tusk length reaches 75 cm. The author notes that although the sample was small, the study provided an initial data set for detailed knowledge on the population structure of southeastern Cameroon’s elephant populations, and he hopes that professional hunting guides will take measurements to supplement it